Environmental planning and management for urban industry : case study of public health effects of industrial air pollution in Map Ta Phut community, Rayong province, Thailand - Choen Krainara; Nguyen Luong Bach; Nurul Amin, A.T.M.; Frankel, Richard, J.; The Oil Refinery Contract Contribution Fund, Thailand; Canadian International Development Agency; Canadian Universities Consortium and (CIDA-CUC) (Bangkok : Asian Institute of Technology, 1999)
In the recent years, Thailand has been enjoying flourished economic growth as a result of decentralization policy to promote rapid industrialization. In response to this policy, Map Ta Phut community was chosen as host of highly industrialized complex namely Map Ta Phut Industrial Estate, where 48 gases and petrochemicals-related industrial plants are located. After operated for over years, such recurring industrial air pollution leakage mainly as Hazardous Air Pollutants (HAPs) in the form of Volatile Organic Compounds (VOCs) were immensely exposed, posing acute health effects to the nearby communities. These major frequent detection were Benzene, Toluene, Styrene and Xylene. This study therefore aims to assess the community health effects possibly related to such exposure on severity, extent of health effects, including the persistence of diseases. This study encompasses 1 7 communities,_ dividing into 4 zones, 3 zones were in the study area as near (1-3 kms from the estate), intermediate (3.5-8 kms) and farther (more than 7.5 krns); and "control area" lies 20 km away. A comparison was made of the prevalent diseases in the areas, in terms of sexes, age group, and persistence of contracting diseases. The significant results then show that school children were the most susceptible group particularly in zone 1, due primarily to the fact that they were exposed both at schools and at home. It was also shown that such persistence diseases for acute health symptoms had appeared in only zone 1 for more than 10 years. Since the last 5-10 years, it was clearly shown health statuses were steadily changed in wide domain in zone 1 and zone 2. Presumably accumulative health effects were possibly begun in this period due to most of acute health effects has steeply developed to become chronic mainly in zone 1. With in the recent 2-4 years, chronic health symptoms are clearly shown to be continued to develop in zone 1, while acute to become chronic health symptoms are being developed in zone 2 and 3, except in control area. In addition, the prevalence of respiratory diseases, nervous system diseases and skin diseases were felt steeply depending on distances from the estate. This comprehensive assessment of health effects finally concludes that the prevalence of the above mentioned diseases might be possibly related to hazardous air pollutants exposure from the estate. Lack of interagency coordination was said to be one of the major obstacle to attain the ultimate goal due to more than four ministries were involved. While each agency was handled its own separate law creating some overlap of jobs, weak institutional capacity and lack of strong rp.onitoring and mitigation measures. On local government side, although being administered for highly industrialized community, yet in fact it was conventionally structured like other municipalities which were facing similar problems in terms of lack of qualified personnel, equipment and expertise. In relation to the role of public, the study reveals that residents are somewhat aware of nearby environmental quality but were facing inadequate information and knowledge to understand how to protect themselves from such exposure. Based on these findings, the study concludes that residence with proximity to the estate were posed higher health risks than those residing farther away. Such recommendations have been made in respond to continue smart growth area in association with promoting healthy community. Different measures were proposed ranging from preventing industrial air pollution exposure, mitigating industrial air pollution, and finally protecting health threats for the long run.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science. School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1999
Keywords: Map Ta Phut Industrial Estate; Industries -- Environmental aspects -- Thailand -- Rayong